On the structure of some minimax-antifinitary modules - V.A. Chupordia (Karpatsʹkì Matematičnì Publìkacìï, 2015)
Let $R$ be a ring and $G$ a group. An $R$-module $A$ is said to be {\it minimax} if $A$ includes a noetherian submodule $B$ such that $A/B$ is artinian. The author study a $\mathbb{Z}_{p^∞}G$-module $A$ such that $A/C_A(H)$ is minimax as a $\mathbb{Z}_{p^∞}$-module for every proper not finitely generated subgroup $H$.